The Old Woman / Grand-Mother ethnolinguistic motif associated with the Mother-Earth figure in Western Europe? Database and analysis of place-names and lexical items - Fossard, Lee (CCSD, 2021)
This work aims at studying the Old Woman (OW) linguistic motif which is highly recurrent, on a European scale, in toponymy, folklore, and semantics. This pattern can be found in the languages and dialects of eight countries constituting our study area: Norway, Denmark, Iceland, the United Kingdom, Ireland, France, Spain, and Portugal. The main goal is to reveal similarities between different cultural and linguistic areas by developing a method which help finding and analysing ethnolinguistic data. Those pieces of information are gathered in a database of more than 7380 items – mostly place-names – the translation of which contains the words “old woman” (OW) or “grand-mother” (GM), the major variant of this motif.The matter here is to show the scientific interest of a toponymic approach that takes into account folklore, mythology, language (semantics) and archaeology (megaliths); in other terms, the rich cultural content of names and places.The Old Woman motif particularly refers to pieces of land, rivers, hilly or mountainous areas and to megaliths. This old woman is present for instance in customs (during New Year's Day or Lent) and in agrarian rituals (during harvest and haymaking).What precisely lies behind the name of “Old Woman” designating, in certain European legends, a giantess carrying and throwing huge boulders?How to interpret the fact that her name is given to animals, plants, and weather phenomena?In order to explain this linguistic persistence, answers will be brought through an interdisciplinary approach. Ce travail vise à rendre compte du motif linguistique Vieille Femme (VF) omniprésent, à l'échelle européenne, en toponymie, en littérature orale et en sémantique lexicale. Il se décline dans les langues et dialectes de huit pays constituant notre zone d'étude : Norvège, Danemark, Islande, Royaume-Uni, Irlande, France, Espagne et Portugal. L'objectif est de révéler des concordances entre des aires culturelles et linguistiques différentes, notamment via l'élaboration d'une méthode de recherche et ...